Analisis butir soal ujian akhir semester mata kuliah psikologi belajar menggunakan software anates - Azzahroh, Sakinah; Iman, Fajar Lilia; Anwar, Badiul; Aziz, Rahmat (UIN Maulana Malik Ibrahim Malang, 2022)
The Final Examination is conducted to test students' understanding of the lecture material that has been taken. The questions given must have a quality so that they can measure learning outcomes appropriately. The purpose of this study was to determine the quality of UAS questions for the Student Learning Psychology subject at X University. This research uses a quantitative descriptive method. Item analysis based on validity, reliability, discriminating power, level of difficulty, and effectiveness of the distractor. The questions consist of 3 types; multiple choice, true-false, and essay. Data collection techniques used the questionnaire method and the results of the data were analyzed using Anates ver.4 software, and Microsoft Excel. The results of the analysis stated that the test questions for the Learning Psychology subject were of good quality. The true-false questions obtained test reliability results of 0.41 and the multiple choice questions obtained 0.46 indicating that the questions had moderate reliability. Distinguishing power of true-false questions has a percentage of 12.50% to 68.75%, multiple choice questions 18.75% to 62.50% and essay questions 15.63% to 29.63% which means the questions have different power ranging from bad to very good. The difficulty level of true and false questions obtained a percentage of 51.67% to 95%, multiple choice questions 33% to 81%, and essay questions 33% to 55% indicating that there were no difficult questions. The effectiveness of the distractor on multiple choice questions 30% has the effectiveness of the less good distractor, 10% which is included in the effectiveness of the good distractor is 50%. Meanwhile, the effectiveness of the deception is very good, 10%. Ujian Akhir Semester dilakukan untuk menguji pemahaman mahasiswa terkait materi perkuliahan yang telah ditempuh. Soal yang diberikan harus memiliki kualitas yang suapaya dapat mengukur hasil belajar dengan tepat. Tujuan dari penelitian ini untuk mengetahui kualitas soal UAS mata kuliah Psikologi Belajar Mahasiswa Universitas X. Adapun penelitian ini menggunakan metode deskriptif kuantitatif. Analisis soal berdasarkan validitas, reliabilitas, daya pembeda, tingkat kesukaran, dan efektivitas pengecoh. Soal terdiri dari 3 tipe; pilihan ganda, benar-salah, dan essay. Tehnik pengumpulan data menggunakan metode kuisioner dan hasil data dianalisis menggunakan software Anates ver.4, dan Microsoft Excel. Hasil dari analisis menyatakan bahwa soal UAS mata kuliah Psikologi Belajar merupakan soal yang berkualitas baik. Soal benar-salah memperoleh hasil reliabilitas tes sebesar 0.41 dan soal pilihan ganda memperoleh angka 0.46 menunjukkan bahwa soal memiiki reliabilitas yang sedang. Daya beda soal benar-salah memiliki persentase 12.50% sampai 68.75% , soal pilihan ganda 18.75% sampai 62.50% dan soal essay 15,63% sampai 29.63%yang berarti soal memiliki daya beda yang beragam mulai jelek hingga baik sekali. Tingkat kesukaran soal benar salah memperoleh persentase 51.67 % sampai 95% , soal pilihan ganda 33% sampai 81%, dan soal essay 33% sampai 55% menunjukan tidak ada soal yang sukar. Efektifitas pengecoh pada soal pilihan ganda 30% memiliki efektivitas pengecoh kurang baik, 10% yang termasuk dalam efektivitas pengecoh baik adalah 50%. Sedangkan soal efektivitas pengecohnya sangat baik 10%. Copyright ©2022. The Authors. Published by Journal of Indonesian Psychological Science (JIPS). This is an open access article under the CC BY NO SA. link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0